2020
DOI: 10.1080/21623945.2020.1859789
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Embryonic Fibroblast Adipogenic Potential: A Comprehensive Transcriptome Analysis

Abstract: Our understanding of adipose tissue has progressed from an inert tissue for energy storage to be one of the largest endocrine organs regulating metabolic homoeostasis through its ability to synthesize and release various adipokines that regulate a myriad of pathways. The field of adipose tissue biology is growing due to this association with various chronic metabolic diseases. An important process in the regulation of adipose tissue biology is adipogenesis, which is the formation of new adipocytes. Investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…While a variety of myosin types are implicated in adipocyte metabolism, little is known about the role of MYH10 in adipocytes and adipogenesis. Previous studies have reported that MYH10 is expressed in adipocytes 29,[35][36][37][38] , and we have previously demonstrated the association of reorganized actin filaments and other candidate proteins, including MYH10, in adipocyte differentiation 6 . However, the mechanism of action and function of MYH10 in adipocytes has never been studied.…”
Section: Introductionmentioning
confidence: 59%
“…While a variety of myosin types are implicated in adipocyte metabolism, little is known about the role of MYH10 in adipocytes and adipogenesis. Previous studies have reported that MYH10 is expressed in adipocytes 29,[35][36][37][38] , and we have previously demonstrated the association of reorganized actin filaments and other candidate proteins, including MYH10, in adipocyte differentiation 6 . However, the mechanism of action and function of MYH10 in adipocytes has never been studied.…”
Section: Introductionmentioning
confidence: 59%
“…As an additional test that HMGN proteins can modulate adipocyte browning, we differentiated mouse embryonic fibroblasts (MEFs) from WT and DKO mice into adipocytes using a cocktail known to facilitate differentiation into brown-like adipocytes 14 , 35 , 36 (Fig. S 8a ).…”
Section: Resultsmentioning
confidence: 99%
“…By using NCBI SRA toolkit, the raw metadata was downloaded from the FASTQ files of Gene Expression Omnibus (GEO) datasets: (i) GSE138242: 20-week old visceral adipose tissue (vAT) from chow diet (CD)-fed mice (n = 3) and high fat diet (HFD)-fed mice (n = 3), 43 (ii) GSE55008: omental adipose tissue (oAT) from lean control (n = 12) and obese patients (n = 12), 44 and (iii) GSE152750: undifferentiated mouse embryo fibroblast (MEF) (n = 3) and differentiated MEF (n = 3) for 5 d in AIM. 45 The transcriptomic RNA-seq was performed using TopHat2 aligner (https://ccb.jhu.edu/softw are/topha t/index.shtml) and Cufflinks assembler (http://cole-trapn ell-lab.github.io/ cuffl inks) with mouse reference gene mm10 and human reference gene hg19. The transcript expression was calculated as Fragments Per Kilobase of transcript per Million fragments mapped (FPKM).…”
Section: Big Data Analysis and Gene Expression Profilesmentioning
confidence: 99%